Analisis Kelangsungan Usaha Budidaya Ikan Lele di Kecamatan Baki Kabupaten Sukoharjo Tahun 2014 - Fajri, Desy Hidayatul, Dra. Umrotun, M. Si, Dra. Retno Woro Kaeksi (2015)
The aims of this research is (1) to determine the characteristics of demographic, social, and economic entrepreneurs of catfish aquaculture in Baki, (2) to identify the factors that affect the continuity business of catfish aquaculture in Baki, (3) to identify the continuity of catfish aquaculture in Baki from 2010-2014 and (4) to identify the contribution of revenues in catfish aquaculture in Baki to the family income. The method used in this research is survey. Data were analyzed using frequency tables and cross-table analysis. The total number of respondents there were 77 respondents. Data used is primary data and secondary data. The primary data is age, sex, marital status, number of dependents, education of the respondents, the main type of work, size of land owned, income, family income, labor origin, the number of initial capital owned, catfish production, and marketing. The secondary data is data monograph village, physical condition, social and economic. The results of this study are (1) demographic characteristics, social and economic respondents are (a) all employers of catfish aquaculture in Baki is productive age (15-64 years), (b) mostly male, there are 59 respondents (76.62%), (c) the marital status is married, there are 67 respondents (87.01%), (d) has a number of family dependents bit which ranges from 3-<4 people (53.25%), (e) has a level low education, there are 49 respondents (63.60%), (f) agricultural land being, which amounted to 48 respondents (62.34%), (g) has the primary job is a farmer, there are 29 respondents (37.66%), (h) have a household income that is small, there are 38 respondents (49.35%), (i) have a long effort being that of 44 respondents or 57.14%. (2) factors that affect the catfish aquaculture in the study area include low capital, there are 43 respondents (55.84%), lower raw material or seed, there are 45 respondents (58.44%), low the labour, there are 45 respondents (58.40%), and the low maintenance aspect, there are 43 respondents (55.84%), (3) the continuity of catfish aquaculture in the study area low in terms of the parameters of capital, raw materials, labor, maintenance, and income, and (4) contribution of fish aquaculture business income against total income of the family is that of 47 respondents (67.50 %) and have donated between> 26.50% - 46.50%.